Pemodelan Tren Pendapatan Game Gacha Menggunakan Regresi Linier - Yosua Tambunan; Yudi Yohannes; Sardo Sipayung (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2026)
The rapid growth of the digital gaming industry, particularly games with gacha monetization systems, has resulted in highly fluctuating revenue patterns over time. Game revenue does not always follow a linear trend, as it is influenced by various factors such as in-game events, content updates, and player behavior. This study aims to analyze the effect of time variables (months) on the revenue of three popular gacha games, namely Genshin Impact, Honkai: Star Rail, and Zenless Zone Zero. This research employs a quantitative approach using simple linear regression analysis. The data used in this study are secondary data in the form of monthly revenue collected from AppMagic, covering the period from January to December 2025. The results indicate that all three games have negative regression coefficients, suggesting a declining revenue trend over time. However, the coefficient of determination values are relatively low, indicating that the time variable has a very limited ability to explain revenue variation. These findings suggest that gacha game revenue is not significantly influenced by time alone but is driven by other non-linear factors. Therefore, simple linear regression can only provide a general trend and is insufficient to fully describe the dynamics of gacha game revenue.